Early post‐operative diet upgrade in older patients may improve energy and protein intake but patients still eat poorly: an observational pilot study. Issue 6 (27th June 2018) - Byrnes, A.; Worrall, J.; Young, A.; Mudge, A.; Banks, M.; Bauer, J.
Abstract: Background: Malnutrition is prevalent across acute care facilities, particularly in older patients, and contributes to poor surgical outcomes. Clinical practice guidelines recommend the early reintroduction of a full oral diet post‐operatively. The present study aimed to compare estimated energy (EEI) and protein (EPI) intake of patients who received early diet upgrade with those who did not. Methods: Patients ≥65 years admitted post‐operatively to general surgical wards were included. EEI and EPI were calculated and dichotomised as meeting ≥50% or <50% estimated energy (EER) and protein (EPR) requirements. Mean intake and proportion of patients meeting <50% estimated requirements were compared between those who received early upgrade and those who did not at post‐operative day (POD)2. Results: Thirty‐four patients [mean (SD) age 72.9 (5.7) years, 59% male] were analysed at POD2 [EEI: mean 4.2 (2.6) MJ day –1, 56% ( n = 19) met ≥50% EER; EPI: mean 38.7 (29.5) g day –1, 26% ( n = 9) met ≥50% EPR]. The majority ( n = 25, 74%) were upgraded to a nonfluid diet by POD2. More patients on fluid diets consumed <50% EER ( P = 0.025) and <50% EPR ( P = 0.073). No patient on a fluid diet met ≥50% of EPR. Conclusions: Although the majority of older patients received early diet upgrade and these patients consumed more energy and protein than those on fluid diets, as a whole, older patients ate poorly post‐operatively. Fluid diets should therefore not be used indiscriminately and other approaches to improve post‐operative intake of older patients, such as fortified diets, oral nutritional supplements and meal environment interventions, should be adopted.